A Green, Scalable, and Catalyst-Free One-Minute Synthesis of Quinoxalines - Elumalai, Vijayaragavan; Hansen, Jørn H. (SynOpen, 2021)
A highly efficient and catalyst-free protocol is reported for the synthesis of quinoxalines via the classical cyclocondensation reaction between aryldiamines and dicarbonyl compounds. Remarkably simple and green reaction conditions employing methanol as solvent afforded medium to excellent yield of quinoxalines after only one-minute reaction time at ambient temperature. The conditions allow at least 10 gram scale synthesis of quinoxalines and should be a preferred starting point for optimization and method of choice for applications in the synthetic community.
Keywords: quinoxaline; diamine; condensation; diketone; green